The Relationship Between Work Stress, Management And Family Support On Work-Life Balance - Yeo, Ching Ching (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Work-life balance is the common phrase that we always heard in society nowadays. But how many people really knows what's the definition and how to measure whether an individual has balance between work life and family life. There are different perspectives from different individual according to their priorities. For an instance, a fresh graduate's aim gets higher achievement in their career, their priorities will be work. Hence, the time for their career will be longer than time spend on their family. This research proposal is going to study the relationship between work stress, management and family support on work-life balance. In this research, relationship between work stress, management and family support on work-life balance will be investigate through a close-ended questionnaire. This research is a quantitative research which data is collected through questionnaire. 59 respondents in a private organization in Mukah, Sarawak involved in the questionnaire. Hypotheses are tested by using Pearson Correlation with SPSS software. The results showed that the hypotheses alternatives are failed to reject. This study is going to contribute further information on the relationship between work stress, management and family support on work-life balance. This study can raise apprehension of employer on the level of importance of work-life balance in the organization.